Developing a mobile application with geo-analytic tools to perform real estate valuation within smart cities - Aydınoğlu, Arif Çağdaş; Bovkir, Rabia; Çölkesen, İsmail; Seyrek, Eren Can; Bilgin, Mehmet Selim (Taylor & Francis Ltd, 2025)
Urban land management policies and applications require comprehensive information about real estate development dynamics and value criteria. In this study, geo-analytic tools and a mobile app were produced for residential property valuation in smart cities. Geo-analytical tools were automated to process and use datasets extracted from the databases and 'Smart Real Estate' mobile app using data sets produced by the developed geo-analytics tools shares map services automatically. In this way, users can get real-time location data via web services by triggering geographic analysis tools at certain intervals. It can manage and analyse big geographic data to share smart city services about real estate to citizens.
Keywords: Smart city; Urban land valuation; Geographic analytics; Mobile GIS application; Geo-analytic tools